Pelatihan Pembelajaran dan Penilaian Berbasis HOTS Bagi Guru SD Se-Kecamatan Mantrijeron Kota Yogyakarta - Muhammad Nur Wangid; Ali Mustadi; Amir Syamsudin; Woro Sri Hastuti; Ningrum Perwitasari; Ady Ferdian Noor; Eni Kusrini; Yogi Prihandoko (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Higher Order Thinking Skills (HOTS) is a way that puts forward critical and creative values ​​so that it is seen as being able to provide solutions in facing the times. The method used is descriptive to describe HOTS-based learning and assessment. The purpose of this activity is to improve the ability of elementary school (SD) teachers in designing HOTS-based learning tools consisting of lesson plans and HOTS-based assessments. This activity is motivated by the skills faced by elementary school teachers in the implementation of the 2013 curriculum, especially in designing and implementing HOTS-based learning, as well as developing HOTS-based assessments. Therefore, this activity aims to make teachers become professionals in educating elementary students in developing children's thinking skills at a higher level.